Rubber band training improves athletic performance in young female handball players - Gaamouri, N.; Hammami, M.; Cherni, Y.; Oranchuk, D.; van den Tillaar, R.; Chelly, M. S. (Journal of Human Kinetics, 2024)
This study's objective was to investigate the impact of a 10-week in season contrast rubber band training program on athletic performance in young female handball players. Youth athletes (15.8 ± 0.2 years) were randomly assigned to an intervention (n = 16) or a control group (n = 14). The intervention group performed contrast rubber band training (20 sessions over two weeks), while the control group maintained regular in-season training. The modified T-test, squat jump, countermovement jump, standing long jump, repeated sprint ability, 1-RM bench press and half squat, along with upper and lower limb force-velocity tests were performed. The intervention group experienced significantly larger performance enhancements than the control group in the modified T-test [p < 0.001; d = 1.45 %delta (intervention = -7.1, control = -0.8)], vertical jump [p = 0.009; d = 0.72; %delta (8.4 < intervention < 19.8, 4.1 < control < 12.2)], 1-RM strength [p = 0.04, d = 0.80; %delta (37.1 < intervention < 39.7, 7.2 < control < 11.2)], all force-velocity scores for the upper limbs [p = 0.009; d = 0.72; %? (21 < intervention < 82, 0.1 < control < 11.6)], three of four force-velocity scores for the lower limb performance [p = 0.02; d = 0.64; %delta (6.4 < intervention < 31.3, 0.8 < control < 11.1)] and all repeated sprint times [p < 0.001; d = 1.15; %delta (-3.4 < intervention < -3.1, -1.9 < control < -0.5)]. It was concluded that ten weeks of contrast rubber band training positively affected most motor abilities in youth female handball athletes. Therefore, coaches and practitioners should consider utilizing contrast rubber band strength training as a time and resource-efficient means of improving physical fitness of youth handball players.